A Quartic System

Поделиться
HTML-код
  • Опубликовано: 7 фев 2025
  • 🤩 Hello everyone, I'm very excited to bring you a new channel (SyberMath Shorts).
    Enjoy...and thank you for your support!!! 🧡🥰🎉🥳🧡
    / @sybermath
    / @aplusbi
    ⭐ Join this channel to get access to perks:→ bit.ly/3cBgfR1
    My merch → teespring.com/...
    Follow me → / sybermath
    Subscribe → www.youtube.co...
    ⭐ Suggest → forms.gle/A5bG...
    If you need to post a picture of your solution or idea:
    in...
    #algebra #polynomials #exponentials #logs #trigonometry #calculus
    via @RUclips @Apple @Desmos @NotabilityApp @googledocs @canva
    PLAYLISTS 🎵 :
    ▶ Trigonometry: • Trigonometry
    ▶ Algebra: • Algebra
    ▶ Complex Numbers: • Complex Numbers
    ▶ Calculus: • Calculus
    ▶ Geometry: • Geometry
    ▶ Sequences And Series: • Sequences And Series

Комментарии •

  • @user-dq6jf9ru9e
    @user-dq6jf9ru9e 6 месяцев назад +4

    I think the 2nd method could've been even easier if we'd noticed here (6:21) not only (x+y)⁴=... but (x-y)⁴=... also.
    We'd come to (x+y)⁴=81 and (x-y)⁴=1, then x+y=±3 and x-y=±1 and get the answer without solving quadratic equations.

    • @erikroberts8307
      @erikroberts8307 6 месяцев назад +2

      I know. Before the first method was even started, I was able to solve this problem in my head using this approach. But I still like the other methods he came up with to solve it. Very interesting.

  • @bobkurland186
    @bobkurland186 6 месяцев назад +1

    if you switch to variables u = (x^2 +y^2) and v = xy, it becomes easier to solve. you can get your equations for s and p without solving for x+y.

  • @HenkVanLeeuwen-i2o
    @HenkVanLeeuwen-i2o 5 месяцев назад

    The 2nd equation can be solved for y^2 in terms of x using the quadratic formula.

  • @williamspostoronnim9845
    @williamspostoronnim9845 6 месяцев назад

    Блестяще решенная очень интересная задача!

  • @VictorPensioner
    @VictorPensioner 6 месяцев назад

    (1) xy (x² + y²) = 10
    (2) (x² + y²) + 4x²y² = 41
    From (1)
    (3) (x² + y²) = 10 / xy (x ≠ 0, y≠ 0)
    Substitute (3) in (2)
    [10/xy]² + 4x²y² = 41
    Let
    t = x²y²
    Then
    100/t + 4t = 41
    or
    4t² - 41t + 100
    t₁,₂ = [41 ± √(41² - 1600)] / 8 = (41 ± √81) / 8 = (41 ± 9)/ 8
    Therefore
    x²y² = 4
    or
    x²y² = 50/8 = 25/4
    ------------------
    Case 1.
    x²y² = 4
    ------------------
    From (2)
    (x² + y²)² = 41 - 4x²y² = 41 - 16 = 25
    For equations
    (x² + y²) = 5
    x²y² = 4
    apply Viete formula to x² and y²:
    z² -5z + 4 = 0
    z₁,₂ = [5 ± √(5² - 16)] / 2 = (5 ± √9) / 2 = (5 ± 3)/ 2
    Therefore
    x² = 4, y² = 1
    or
    x² = 1, y² = 4
    From (1) x and y has the same sign
    (x,y) --> (2, 1), (-2, -1), (1, 2), (-1, -2)
    ------------------
    Case 2.
    x²y² = 25/4
    ------------------
    From (2)
    (x² + y²)² = 41 - 4x²y² = 41 - 4*(25/4) = 16
    For equations
    (x² + y²) = 4
    x²y² = 25/4
    apply Viete formula to x² and y²:
    z² -4z + 25/4 = 0
    or
    4z² -16z + 25 = 0

    b² - 4ac= 16² -4*4*25 < 0 no real solutions
    All solutions are
    (x,y) --> (2, 1), (-2, -1), (1, 2), (-1, -2)

  • @yoav613
    @yoav613 6 месяцев назад

    Noice

  • @SidneiMV
    @SidneiMV 6 месяцев назад +1

    x³y + xy³ = 10
    x⁴ + 6x²y² + y⁴ = 41
    (x +y)⁴ = x⁴ + y⁴ + 4(x³y + xy³) + 6x²y²
    (x + y)⁴ = 41 + 4(10) = 81 = 3⁴
    [(x + y)² + 3²][(x + y)² - 3²] = 0
    x³y + xy³ = 10
    xy(x² + y²) = 10
    xy[(x + y)² - 2xy] = 10
    (x + y)² = 9
    xy(9 - 2xy) = 10
    -2(xy)² + 9xy = 10
    2(xy)² - 9xy + 10 = 0
    xy = (9 ± 1)/4
    xy = 5/2 ∨ xy = 2
    (x + y)² = 9 => x + y = ±3
    x + y = 3
    x + y = 2
    t² - 3t + 2 = 0
    t = (3 ± 1)/2 => t = 2 ∨ t = 1
    *(x,y) = {(2, 1), (1, 2)}*
    x + y = -3
    x + y = 2
    t² + 3t + 2 = 0
    t = (-3 ± 1)/2 => t = -1 ∨ t = -2
    *(x,y) = {(-2, -1), (-1, -2)}*
    x + y = 3
    x + y = 5/2
    t² - 3t + 5/2 = 0
    t = (3 ± i)/2
    *(x,y) = {[(3 + i)/2, (3 - i)/2], [(3 - i)/2, (3 + i)/2]}*
    x + y = -3
    x + y = 5/2
    t² + 3t + 5/2 = 0
    t = (-3 ± i)/2
    *(x,y) = {[(-3 + i)/2, (-3 - i)/2], [(-3 - i)/2, (-3 + i)/2]}*
    GENERAL SOLUTION
    *(x,y) = {(2iⁿ, iⁿ), (iⁿ, 2iⁿ)}*
    *(x,y) = {[(3 + i)iⁿ/2, (3 - i)iⁿ/2], [(3 - i)iⁿ/2, (3 + i)iⁿ/2]}*
    n ∈ ℤ